The Light of the Orient - Sharjah Museums Department (Sharjah Museums Department)
Exhibition catalog. Orientalist art in the collection of Sharjah Art Museum.
English; Arabic
Keywords: Medeival; Al Qassimi Collection; N5198-5299 Private collections and collectors; UAE